2013
DOI: 10.2298/fil1302317d
|View full text |Cite
|
Sign up to set email alerts
|

Some fixed point results on weak partial metric spaces

Abstract: The concept of partial metric p on a nonempty set X was introduced by Matthews [13] and it was slightly modified by Heckmann [11] as weak partial metric. In [12], the authors studied fixed point result of new extension of Banach's contraction principle to partial metric space and give some generalized versions of the fixed point theorem of Matthews. In the present paper, we extend and generalize the previous results to weak partial metric spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A classical Banach contraction principle is one of the fundamental results in the fixed point theory, and then several authors have studied to generalize and improve the fixed point theory by applying new contractive conditions for operators and by replacing complete metric spaces with various abstract spaces (see e.g. [1], [7], [18], [22]).…”
Section: Stability Of (3) By Fixed Point Methodsmentioning
confidence: 99%
“…A classical Banach contraction principle is one of the fundamental results in the fixed point theory, and then several authors have studied to generalize and improve the fixed point theory by applying new contractive conditions for operators and by replacing complete metric spaces with various abstract spaces (see e.g. [1], [7], [18], [22]).…”
Section: Stability Of (3) By Fixed Point Methodsmentioning
confidence: 99%
“…Further, Matthews showed that the Banach Contraction principle is valid in partial metric spaces and can be applied in program verification. After that, many authors studied and generalized the results of Matthews (see, for example, [1,3,5,6]). …”
Section: Application To Weak Partial Metric Spacesmentioning
confidence: 99%
“…For more details, we can refer to [1,6]. (pm1) x = y if and only if p(x, x) = p(y, y) = p(x, y), (pm2) p(x, x) p(x, y),…”
Section: Application To Weak Partial Metric Spacesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1999, Heckmann [10] introduced the notion of weak partial metric spaces, which is a generalization of partial metric spaces. Some results for mappings in weak partial metric spaces have been recently obtained by [2] and [4].…”
Section: Introductionmentioning
confidence: 99%